Coordination of N 2 -fixing cell specialization and patterning in filamentous cyanobacteria by a uniquely structured σ factor - Xi Hu; Xujiao Liu; Yali Wang; Ke Liu; Hong Gao; Geqian Zhu; Shuai Wang; Xiantao Fang; Hong Sun; Fang Zhou; Shuiling Ji; Congzhao Zhou; et al. (Proceedings of the National Academy of Sciences, 2026)
Cell differentiation and Turing-like patterning are tightly associated in a group of filamentous cyanobacteria that differentiate specialized N 2 -fixing cells, called heterocysts. Based on systematic genetic analyses, in particular genome-wide identification of recognized promoters and assays with a reconstituted Anabaena transcription system in Escherichia coli , we established HetZ as the central activator of the gene regulatory network of heterocyst differentiation. Biochemical and cryo-EM analyses further established HetZ as a σ factor (σ HetZ ). Unique domain insertions in σ HetZ are involved in promoter DNA recognition-unwinding and interaction with the inhibitor PatU3. σ HetZ -PatU3 and the master regulator-diffusible inhibitor constitute the minimal core regulatory circuit (CRC) for cell fate determination and patterning. σ HetZ activates not only genes of the CRC but also downstream regulator/effector genes involved in morphological and functional development. The gene regulatory network and the structure–function relationship of σ HetZ depict how cell differentiation and patterning are coordinated in this group of multicellular cyanobacteria.